NEW
New Website Launch
Experience the best way to solve previous year questions with mock tests (very detailed analysis), bookmark your favourite questions, practice etc...
1

JEE Main 2021 (Online) 27th August Morning Shift

Numerical
If $${y^{1/4}} + {y^{ - 1/4}} = 2x$$, and

$$({x^2} - 1){{{d^2}y} \over {d{x^2}}} + \alpha x{{dy} \over {dx}} + \beta y = 0$$, then | $$\alpha$$ $$-$$ $$\beta$$ | is equal to __________.
Your Input ________

Answer

Correct Answer is 17

Explanation

$${y^{{1 \over 4}}} + {1 \over {{y^{{1 \over 4}}}}} = 2x$$

$$ \Rightarrow {\left( {{y^{{1 \over 4}}}} \right)^2} - 2x{y^{\left( {{1 \over 4}} \right)}} + 1 = 0$$

$$ \Rightarrow {y^{{1 \over 4}}} = x + \sqrt {{x^2} - 1} $$ or $$x - \sqrt {{x^2} - 1} $$

So, $${1 \over 4}{1 \over {{y^{{3 \over 4}}}}}{{dy} \over {dx}} = 1 + {x \over {\sqrt {{x^2} - 1} }}$$

$$ \Rightarrow {1 \over 4}{1 \over {{y^{{3 \over 4}}}}}{{dy} \over {dx}} = {{{y^{{1 \over 4}}}} \over {\sqrt {{x^2} - 1} }}$$

$$ \Rightarrow {{dy} \over {dx}} = {{4y} \over {\sqrt {{x^2} - 1} }}$$ .... (1)

Hence, $${{{d^2}y} \over {d{x^2}}} = 4{{\left( {\sqrt {{x^2} - 1} } \right)y' - {{yx} \over {\sqrt {{x^2} - 1} }}} \over {{x^2} - 1}}$$

$$ \Rightarrow ({x^2} - 1)y'' = 4{{({x^2} - 1)y' - xy} \over {\sqrt {{x^2} - 1} }}$$

$$ \Rightarrow ({x^2} - 1)y'' = 4\left( {\sqrt {{x^2} - 1} y' - {{xy} \over {\sqrt {{x^2} - 1} }}} \right)$$

$$ \Rightarrow ({x^2} - 1)y'' = 4\left( {4y - {{xy'} \over 4}} \right)$$ (from I)

$$ \Rightarrow ({x^2} - 1)y'' + xy' - 16y = 0$$

So, | $$\alpha$$ $$-$$ $$\beta$$ | = 17
2

JEE Main 2021 (Online) 27th July Morning Shift

Numerical
If $$y = y(x),y \in \left[ {0,{\pi \over 2}} \right)$$ is the solution of the differential equation $$\sec y{{dy} \over {dx}} - \sin (x + y) - \sin (x - y) = 0$$, with y(0) = 0, then $$5y'\left( {{\pi \over 2}} \right)$$ is equal to ______________.
Your Input ________

Answer

Correct Answer is 2

Explanation

$$\sec y{{dy} \over {dx}} = 2\sin x\cos y$$

$${\sec ^2}ydy = 2\sin xdx$$

$$\tan y = - 2\cos x + c$$

$$c = 2$$

$$\tan y = - 2\cos x + 2 \Rightarrow $$ at $$x = {\pi \over 2}$$

$$\tan y = 2$$

$${\sec ^2}y{{dy} \over {dx}} = 2\sin x$$

$$ \therefore $$ $$5{{dy} \over {dx}} = 2$$
3

JEE Main 2021 (Online) 27th July Morning Shift

Numerical
Let $$F:[3,5] \to R$$ be a twice differentiable function on (3, 5) such that $$F(x) = {e^{ - x}}\int\limits_3^x {(3{t^2} + 2t + 4F'(t))dt} $$. If $$F'(4) = {{\alpha {e^\beta } - 224} \over {{{({e^\beta } - 4)}^2}}}$$, then $$\alpha$$ + $$\beta$$ is equal to _______________.
Your Input ________

Answer

Correct Answer is 16

Explanation

$$F(3) = 0$$

$${e^x}F(x) = \int\limits_3^x {(3{t^2} + 2t + 4F'(t))dt} $$

$${e^x}F(x) + {e^x}F'(x) = 3{x^2} + 2x + 4F'(x)$$

$$({e^x} - 4){{dy} \over {dx}} + {e^x}y = (3{x^2} + 2x)$$

$${{dy} \over {dx}} + {{{e^x}} \over {({e^x} - 4)}}y = {{(3{x^2} + 2x)} \over {({e^x} - 4)}}$$

$$y{e^{\int {{{{e^x}} \over {({e^x} - 4)}}dx} }} = \int {{{(3{x^2} + 2x)} \over {({e^x} - 4)}}{e^{\int {{{{e^x}} \over {{e^x} - 4}}dx} }}dx} $$

$$y.({e^x} - 4) = \int {(3{x^2} + 2x)dx + c} $$

$$y({e^x} - 4) = {x^3} + {x^2} + c$$

Put x = 3 $$\Rightarrow$$ c = $$-$$36

$$F(x) = {{({x^3} + {x^2} - 36)} \over {({e^x} - 4)}}$$

$$F'(x) = {{(3{x^2} + 2x)({e^x} - 4) - ({x^3} + {x^2} - 36){e^x}} \over {{{({e^x} - 4)}^2}}}$$

Now, put value of x = 4 we will get $$\alpha$$ = 12 & $$\beta$$ = 4
4

JEE Main 2021 (Online) 27th July Evening Shift

Numerical
Let y = y(x) be the solution of the differential equation dy = e$$\alpha$$x + y dx; $$\alpha$$ $$\in$$ N. If y(loge2) = loge2 and y(0) = loge$$\left( {{1 \over 2}} \right)$$, then the value of $$\alpha$$ is equal to _____________.
Your Input ________

Answer

Correct Answer is 2

Explanation

$$\int {{e^{ - y}}} dy = \int {{e^{\alpha x}}} dx$$

$$ \Rightarrow {e^{ - y}} = {{{e^{\alpha x}}} \over \alpha } + c$$ ..... (i)

Put (x, y) = (ln2, ln2)

$${{ - 1} \over 2} = {{{2^\alpha }} \over \alpha } + C$$ ..... (ii)

Put (x, y) $$ \equiv $$ (0, $$-$$ln2) in (i)

$$ - 2 = {1 \over \alpha } + C$$ ..... (iii)

(ii) $$-$$ (iii)

$${{{2^\alpha } - 1} \over \alpha } = {3 \over 2}$$

$$\Rightarrow$$ $$\alpha$$ = 2 (as $$\alpha$$ $$\in$$ N)

Joint Entrance Examination

JEE Main JEE Advanced WB JEE

Graduate Aptitude Test in Engineering

GATE CSE GATE ECE GATE EE GATE ME GATE CE GATE PI GATE IN

Medical

NEET

CBSE

Class 12